2017
DOI: 10.3390/molecules22101734
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic Diversity and Structure Pattern of Indigofera Pseudotinctoria in Karst Habitats of the Wushan Mountains Using AFLP Markers

Abstract: Indigofera pseudotinctoria Mats is an agronomically and economically important perennial legume shrub with a high forage yield, protein content and strong adaptability, which is subject to natural habitat fragmentation and serious human disturbance. Until now, our knowledge of the genetic relationships and intraspecific genetic diversity for its wild collections is still poor, especially at small spatial scales. Here amplified fragment length polymorphism (AFLP) technology was employed for analysis of genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Therefore, geographical barriers of the mountain systems limit the gene flow between eastern populations and other populations of C. oliveri. Similar results have been found in the studies of Actinidia chinensis (Li et al, 2010), Castanea mollissima (Liu et al, 2013), and Indigofera pseudotinctoria (Fan et al, 2017), which suggested that these mountain systems acted as barriers and caused genetic isolation. Previous studies have identified the Wumeng Mountains as an obvious geographical barrier, which can promote genetic differentiation among populations of other species (Gong et al, 2011;Wang et al, 2011).…”
Section: Population Divergence and Structuresupporting
confidence: 87%
“…Therefore, geographical barriers of the mountain systems limit the gene flow between eastern populations and other populations of C. oliveri. Similar results have been found in the studies of Actinidia chinensis (Li et al, 2010), Castanea mollissima (Liu et al, 2013), and Indigofera pseudotinctoria (Fan et al, 2017), which suggested that these mountain systems acted as barriers and caused genetic isolation. Previous studies have identified the Wumeng Mountains as an obvious geographical barrier, which can promote genetic differentiation among populations of other species (Gong et al, 2011;Wang et al, 2011).…”
Section: Population Divergence and Structuresupporting
confidence: 87%
“…It is essential to study the morphological variation, genetic diversity, and population structure to provide basic information on plant conservation (Feng, Wang & Gong, 2014; Fan et al, 2017). Climate change, the rapid growth of the human population, and economic development all contribute to the deterioration of V. rotundifolia’s habitat, reducing the number of individuals in some populations.…”
Section: Discussionmentioning
confidence: 99%
“…Diversity of an intended crop can be investigated by both, phenotypic traits and DNA-based methods such as Restriction Fragment Length Polymorphism (RFLP), Random Amplified Polymorphic DNA (RAPD), Amplified Fragment Length Polymorphism (AFLP), microsatellites and Single Nucleotide Polymorphism (SNP) (Bhandari et al, 2017). AFLP has been applied for genetic diversity studies in a wide range of plant species including teak (Vaishnaw et al, 2015), orchardgrass (Zhang et al, 2018), potato (Bryan et al, 2017), legume shrub (Fan et al, 2017), winged bean (Mohanty et al, 2019), blackberry (Garrido et al, 2020), Jatropha (Avendaño et al, 2015) and Brassica oleracea (El-Esawi et al, 2016). The main advantage of AFLP markers is that several loci can be assayed simultaneously, where the technique is amenable to automation and more importantly shows high stability and reproducibility (Thaipong et al, 2017;Todd et al, 2011) In this study, the genetic variability of 67 oil palm breeding populations in Malaysia was estimated by employing eight AFLP primer combinations.…”
Section: P R E S Smentioning
confidence: 99%